Prediction of novel alloy phases of Al with Sc or Ta - Bilic, Ante; Gale, Julian; Gibson, Aaron; Wilson, N.; McGregor, K. (Nature Publishing Group, 2015)
Using the evolutionary optimization algorithm, as implemented in the USPEX crystal predictor program, and first principles total energy calculations, the compositional phase diagrams for Al-Sc and Al-Ta alloy systems at zero temperature and pressure have been calculated. In addition to the known binary intermetallic phases, new potentially stable alloys, AlSc3 and AlTa7, have been identified in the Al-poor region of the phase diagram. The dynamic and thermal stability of their lattices has been confirmed from the calculated vibrational normal mode spectra in the harmonic approximation.